(untitled) (University Journal of Zoology, Rajshahi University, 2007)
Key words: Flavobacterium psychrophilum; colony forming unit, diluent; viable count; serial dilution Univ. j. zool. Rajshahi Univ. Vol.21, 2002. pp. 81-83